Enhancing energy efficiency in severe cold plateau regions: Atrium design strategies for zero energy houses - Yanxia Li; Xing Guo; Yuqian Hong; Gang Yao (Case Studies in Thermal Engineering)
With the global emphasis on sustainable development and energy conservation, zero energy houses are gradually becoming a research hotspot in the field of architecture. This study explores the potential impact of atrium design on energy-saving performance, using T&A House, a zero energy house (ZEB) in a severe cold plateau region of China, as a case study. Through simulation analysis, we found that transforming the atrium into a central courtyard leads to an increase in annual cooling demand (ACC) by 431.31 kW h (a 44.64 % increase) and annual heating demand (AHC) by 1480.1 kW h (a 21.91 % increase). Further optimization of the section aspect ratio (SAR), shading design, and window-to-wall ratio of the atrium resulted in a reduction of heating demand by 1565.4 kW h (a 19.01 % decrease) and cooling demand by 749.91 kW h (a 53.66 % decrease) compared to the courtyard. The results show that the energy efficiency of zero energy houses can be significantly improved by well-designed atriums, offering a new energy-saving strategy for the design of houses in severe cold plateau regions.